COMMUNICATING RESEARCH FINDINGS IN BASIC SCIENCE AND TECHNOLOGY FOR TECHNOLOGICAL DEVELOPMENT - Babayemi, John Olakunle; Utibe, Uduak James (MATTER: International Journal of Science and Technology, 2017)
Communicating research findings in science education and in particular, basic science and technology seem to witness some sorts of ‘statistical jargons’ and lots of complexities with respect to the terms, methods, and language of communicating the results. For decades, lots of research work in Nigeria and outside Nigeria have been directed towards improving the standard and statuesque of science education for the scientific and technological advancement of the nation. The expected impacts of these robust findings on users and the overall outcomes on the technological development of the nation are not encouraging. The reasons could be attributed to the difficulty in interpreting the research results and the form the results are communicated to the users. Research results perhaps and sincerely should have been weapons for greater achievements in our science classrooms for scientific and technological developments of the nation at large. Study of this nature ensures that research findings have an impact on practice and practitioners including researchers, science teachers, professional trainees and non-professional readers for expected outputs. This paper therefore addressed communicating research findings in basic science and technology implications for professional trainees and non-professional readers and technological development. Finally, recommendations are made.